Model of an intelligent energy harvesting system from microbial fuel cells in wastewater treatment process - Ngoc-Thinh Quach; Thieu Quang Quoc Viet; Pham Van Toan; Minh-Trung Dao (Institute of Advanced Engineering and Science, 2021)
This paper presents a model of an intelligent energy harvesting system from microbial fuel cells (MFCs) in the wastewater treatment process. The model consists of two direct current (DC/DC) converters connected in a cascade. One DC/DC converter is used to capture energy from MFC and store it in a supercapacitor. The other DC/DC converter is responsible for increasing the low output voltage to a higher voltage level. In the paper, the MFC is modeled by a DC voltage source instead of a real MFC that contains wastewater inside it. The experimental results demonstrate that the model of an intelligent energy harvesting system can increase the low output voltage of MFC up to 3.3 V and achieve intermittent output power at a high level that can use in practice.